Electrochemical device and electronic device

By using lithium transition metal composite oxide as the positive electrode active material in an electrochemical device and combining the design of B and M elements, the problems of structural stability and cyclic performance of the electrochemical device at high voltage are solved, and high energy density and Improved security.

CN119278517AActive Publication Date: 2025-01-07NINGDE AMPEREX TECHNOLOGY LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380039254.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-01-07
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

After the existing electrochemical devices increase the working voltage, they are prone to problems such as oxygen release of the positive electrode material, electrolyte decomposition, battery cell gas production and circulating dive, and it is difficult to have high energy density, long cycle performance and high safety.

Method used

Lithium transition metal composite oxide is used as the positive electrode active material, including Ni, Mn, B and M elements (where M is Na or K). The capacity voltage differential curve of the electrochemical device is above 4.1V It has characteristic peaks, the B element coating inhibits surface oxygen release, and the M element is deposited on the negative electrode during charging and discharging, promoting film formation and stability of the solid electrolyte interface film.

Benefits of technology

It improves the structural stability and energy density of the electrochemical device at high voltage, improves the cycling performance and high-temperature storage performance, reduces the electrolyte decomposition and side reactions, and improves the safety and kinetic performance of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278517A_ABST
    Figure CN119278517A_ABST
Patent Text Reader

Abstract

An electrochemical device and an electronic device. The electrochemical device comprises a positive pole piece. The positive pole piece comprises a positive active material layer, the positive active material layer comprises a positive active material, the positive active material comprises a lithium transition metal composite oxide, the lithium transition metal composite oxide contains an Ni element, an Mn element, a B element and an M element, and the M element comprises at least one of an Na element and a K element. The electrochemical device is charged and discharged at a current of 0.2 C. The relation curve between the discharge capacity voltage differential dQ / dV of the electrochemical device and the voltage V has a characteristic peak at 4.1 V or more. The electrochemical device can have both high energy density and excellent cycle performance and high-temperature storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage, and in particular to electrochemical devices and electronic devices. Background Art

[0002] As the market demand for long battery life of electronic devices continues to increase, it is urgent to improve the energy density of electrochemical devices (e.g., lithium-ion batteries). Increasing the operating voltage is an effective way to improve the energy density of electrochemical devices. However, increasing the operating voltage may lead to problems such as oxygen release from the cathode material, electrolyte decomposition, gas production from the battery cell, and cycle jump. Therefore, it is urgent to develop an electrochemical device with high energy density, long cycle performance, and high safety. Summary of the invention

[0003] In view of this, the present application provides an electrochemical device and an electronic device to improve the cycle performance and safety performance of the electrochemical device while having high energy density.

[0004] In the first aspect of the present application, an electrochemical device is provided, the electrochemical device comprising a positive electrode plate. The positive electrode plate comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises a lithium transition metal composite oxide, the lithium transition metal composite oxide contains Ni element, Mn element, B element and M element, wherein the M element comprises at least one of Na element or K element. The electrochemical device is charged and discharged with a current of 0.2C, and the relationship curve between the capacity voltage differential dQ / dV and the voltage V of the electrochemical device discharge has a characteristic peak above 4.1V. The electrochemical device of the present application, on the one hand, because the positive electrode active material is doped with the M element, the structural stability of the positive electrode active material under high voltage can be improved. At the same time, due to the presence of oxygen vacancies on the surface of the positive electrode active material, the surface oxygen release of the positive electrode active material is suppressed, so that the electrochemical device has a reversible discharge capacity in the high voltage range, thereby greatly improving the energy density of the electrochemical device. On the other hand, the B element contained in the positive electrode active material is coated on the surface of the positive electrode active material, which can further inhibit the surface oxygen release of the positive electrode active material, reduce the direct contact between the electrolyte and the surface of the positive electrode active material, inhibit the decomposition of the electrolyte and the occurrence of side reactions, thereby improving the cycle performance and high-temperature storage performance of the electrochemical device.

[0005] In some embodiments, in the lithium transition metal composite oxide, the molar content of the B element is a, the molar content of the Ni element is b, the molar content of the Mn element is c, and the molar content of the M element is d. In some embodiments, 0.01≤a / (b+c)≤0.1. Further, in some embodiments, 0.02≤a / (b+c)≤0.07. In this way, the surface oxygen release of the positive electrode active material can be better suppressed, and the cycle performance and high temperature storage performance of the electrochemical device can be improved.

[0006] In some embodiments, 0.01≤d / (b+c)≤0.15. Further, in some embodiments, 0.03≤d / (b+c)≤0.08. In this way, the structural stability of the positive electrode active material under high voltage can be further improved, and the impact on the capacity of the electrochemical device can be reduced.

[0007] In some embodiments, 0.3≤b / (b+c)≤0.7. In this way, the discharge capacity of the positive electrode active material can be increased, thereby increasing the energy density of the electrochemical device.

[0008] In some embodiments, the electrochemical device also includes a negative electrode plate. When the electrochemical device is in a fully charged state, the molar content of the M element in the negative electrode plate is e, and the molar content of the Li element is f, satisfying: 0.03≤e / f≤0.09. In the electrochemical device of the present application, the M element introduced into the positive electrode active material will dissolve from the positive electrode during the formation and subsequent charge and discharge processes, and will be deposited on the negative electrode through the electrolyte, so that the solid electrolyte interface (SEI) film component on the surface of the negative electrode contains carbonates of the M element. The carbonates of the M element have high electron affinity, which promotes the continuous growth of the SEI film and optimizes the film formation process of the SEI film on the surface of the negative electrode, making the formed SEI film denser and more stable, while improving the viscoelasticity and flexibility of the SEI film and reducing surface cracks. In addition, the carbonates of the M element can enhance Li + It can also reduce the decomposition and gas production of the electrolyte on the negative electrode side during cycling and high-temperature storage, thereby improving the cycling performance and high-temperature storage performance of the electrochemical device.

[0009] In some embodiments, when the electrochemical device is in a fully charged state, the molar content of the M element in the lithium transition metal composite oxide is g, and the molar content of the Li element is h, satisfying: 0.02≤g / h≤0.1. In this way, the electrochemical device can be promoted to have both high energy density and good cycle and high temperature storage performance.

[0010] In some embodiments, when the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has a diffraction peak A in the range of 36° to 37.5°, and the peak intensity of the diffraction peak A is I A , has a diffraction peak B in the range of 43.5° to 45°, and the peak intensity of the diffraction peak B is I B , satisfying: 1.7≤I A / I B ≤2. In this way, the positive electrode active material has good structural stability in the fully charged state, thereby improving the cycle performance and high temperature storage performance of the electrochemical device.

[0011] In some embodiments, the lithium transition metal composite oxide includes a matrix and a coating layer, wherein the matrix includes Ni, Mn and M elements, and the coating layer includes B element. The doping of M element in the matrix improves the structural stability of the positive electrode active material under high voltage; at the same time, the coating layer containing B element can inhibit the surface oxygen release of the positive electrode active material, reduce the direct contact between the electrolyte and the surface of the positive electrode active material, inhibit the decomposition of the electrolyte and the occurrence of side reactions, thereby improving the cycle performance and high temperature storage performance of the electrochemical device.

[0012] In some embodiments, the coating layer comprises a B-containing oxide.

[0013] In some embodiments, the lithium transition metal composite oxide includes secondary particles composed of primary particles, thereby improving the kinetic performance of the electrochemical device.

[0014] In some embodiments, the average diameter of the secondary particles is 6 μm to 14 μm.

[0015] In some embodiments, the interior of the secondary particles includes pores, which can provide a buffer space for the strain of the secondary particles during the charge and discharge process, reduce the risk of secondary particle rupture, and thus improve the cycle performance and high-temperature storage performance of the electrochemical device.

[0016] In some embodiments, the secondary particles have gaps extending from the interior to the surface, which can promote the intercalation and deintercalation of lithium ions in the secondary particles and improve the kinetic performance of the electrochemical device.

[0017] In some embodiments, the lithium transition metal composite oxide has a layered crystal structure belonging to the R-3m space group.

[0018] In some embodiments, the lithium transition metal composite oxide includes Li x1 M x2 Ni y1 Co y2 Mn y3 R y4 B y5 O z1 T z2, 0.6 ≤ x1 ≤ 1.2, 0.01 ≤ x2 ≤ 0.15, 0.3 ≤ y1 ≤ 0.7, 0 ≤ y2 ≤ 0.3, 0.3 ≤ y3 ≤ 0.7, 0 ≤ y4 ≤ 0.2, 0 < y5 ≤ 0.1, 1.8 ≤ z1 ≤ 2.2, 0 ≤ z2 ≤ 0.2, wherein the element M includes at least one of Na or K, the element R includes at least one of Ca, Sr, Ba, Al, Fe, Mg, Si, P, S, Ti, V, Cr, Cu, Zn, Ga, Ge, Zr, Mo, W, Y, Nb, In, Sn, Pb, Sb, Ce, La, Ta or Hf, and the element T includes at least one of F, Cl, Br, I or N.

[0019] In the second aspect of the present application, an electronic device is further provided, which includes the above-mentioned electrochemical device. Description of the Drawings

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the accompanying drawings required for the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present application. For those of ordinary skill in the art, other embodiments can also be obtained based on these drawings.

[0021] Figure 1 It is a scanning electron microscope (SEM) photograph of the cross-section of the positive electrode plate in Embodiment 1 of the present application;

[0022] Figure 2 It is an X-ray diffraction (XRD) pattern of the positive electrode plate in the fully charged state in Embodiment 1 of the present application. Detailed Embodiments

[0023] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are only some embodiments of the present application, rather than all embodiments.

[0024] In the first aspect of the present application, an electrochemical device is provided. The electrochemical device includes a positive electrode plate. The positive electrode plate includes a positive electrode active material layer. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material includes a lithium transition metal composite oxide, and the lithium transition metal composite oxide contains Ni element, Mn element, B element and M element, wherein the M element includes at least one of Na element or K element. When the electrochemical device is charged and discharged at a current of 0.2C, the relationship curve between the differential of the discharge capacity voltage dQ / dV and the voltage V of the electrochemical device has a characteristic peak above 4.1V.

[0025] The electrochemical device of the present application adopts the above-mentioned positive electrode active material in the positive electrode active material layer. On the one hand, since the positive electrode active material is doped with the M element, the structural stability of the positive electrode active material under high voltage can be improved. At the same time, due to the presence of oxygen vacancies on the surface of the positive electrode active material, the surface oxygen release of the positive electrode active material is suppressed, so that the electrochemical device has a reversible discharge capacity in the high voltage range, thereby greatly improving the energy density of the electrochemical device. On the other hand, the B element contained in the positive electrode active material is coated on the surface of the positive electrode active material, which can further suppress the surface oxygen release of the positive electrode active material, reduce the direct contact between the electrolyte and the surface of the positive electrode active material, and suppress the decomposition of the electrolyte and the occurrence of side reactions, which is conducive to improving the cycle performance and high temperature storage performance of the electrochemical device.

[0026] In some embodiments, in the lithium transition metal composite oxide of the present application, the molar content of B is a, the molar content of Ni is b, the molar content of Mn is c, and the molar content of M is d. In some embodiments, 0.01≤a / (b+c)≤0.1. Optionally, a / (b+c) is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or a range consisting of any two of the above. Further, in some embodiments, 0.02≤a / (b+c)≤0.07. In this way, the surface oxygen release of the positive electrode active material can be better suppressed, and the cycle performance and high temperature storage performance of the electrochemical device can be improved.

[0027] In some embodiments, 0.01≤d / (b+c)≤0.15. Optionally, d / (b+c) is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.15 or a range consisting of any two of the above. Further, in some embodiments, 0.03≤d / (b+c)≤0.08. In this way, the structural stability of the positive electrode active material at high voltage can be further improved, and the impact on the capacity of the electrochemical device can be reduced.

[0028] In some embodiments, 0.3≤b / (b+c)≤0.7. In this way, the discharge capacity of the positive electrode active material can be increased, thereby increasing the energy density of the electrochemical device.

[0029] In some embodiments, the electrochemical device also includes a negative electrode plate. When the electrochemical device is in a fully charged state, the molar content of the M element in the negative electrode plate is e, and the molar content of the Li element is f, satisfying: 0.03≤e / f≤0.09. In the electrochemical device of the present application, the M element introduced into the positive electrode active material will dissolve from the positive electrode during the formation and subsequent charge and discharge processes, and will be deposited on the negative electrode through the electrolyte, so that the solid electrolyte interface (SEI) film component on the surface of the negative electrode contains carbonates of the M element. The carbonates of the M element have high electron affinity, which promotes the continuous growth of the SEI film and optimizes the film formation process of the SEI film on the surface of the negative electrode, making the formed SEI film denser and more stable, while improving the viscoelasticity and flexibility of the SEI film and reducing surface cracks. In addition, the carbonates of the M element can enhance Li + It can also reduce the decomposition and gas production of the electrolyte on the negative electrode side during cycling and high-temperature storage, thereby improving the cycling performance and high-temperature storage performance of the electrochemical device.

[0030] In some embodiments, when the electrochemical device is in a fully charged state, in the lithium transition metal composite oxide, the molar content of the M element is g, and the molar content of the Li element is h, satisfying: 0.02≤g / h≤0.1. In this way, the electrochemical device can be promoted to have both high energy density and good cycle and high temperature storage performance.

[0031] In some embodiments, when the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has a diffraction peak A in the range of 36° to 37.5°, and the peak intensity of the diffraction peak A is I A , has a diffraction peak B in the range of 43.5° to 45°, and the peak intensity of the diffraction peak B is I B , satisfying: 1.7≤I A / I B ≤2. In this way, the positive electrode active material has good structural stability in the fully charged state, thereby improving the cycle performance and high temperature storage performance of the electrochemical device. Optionally, I A / I B The range is 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2 or any two of the above.

[0032] In some embodiments, the lithium transition metal composite oxide includes a matrix and a coating layer, the matrix includes Ni, Mn and M elements, and the coating layer includes B element. The doping of M element in the matrix improves the structural stability of the positive electrode active material under high voltage; at the same time, the coating layer containing B element can inhibit the surface oxygen release of the positive electrode active material, reduce the direct contact between the electrolyte and the surface of the positive electrode active material, inhibit the decomposition of the electrolyte and the occurrence of side reactions, thereby improving the cycle performance and high temperature storage performance of the electrochemical device. In some embodiments, the coating layer contains B-containing oxide.

[0033] In some embodiments, the lithium transition metal composite oxide includes secondary particles composed of primary particles, thereby improving the kinetic performance of the electrochemical device.

[0034] In some embodiments, the BET specific surface area of ​​the lithium transition metal composite oxide is greater than 1 m 2 / g.

[0035] In some embodiments, the average diameter of the secondary particles is 6 μm to 14 μm.

[0036] In some embodiments, the interior of the secondary particles includes pores, which can provide a buffer space for the strain of the secondary particles during the charge and discharge process, reduce the risk of secondary particle rupture, and thus improve the cycle performance and high-temperature storage performance of the electrochemical device.

[0037] In some embodiments, the secondary particles have gaps extending from the interior to the surface, which can promote the intercalation and deintercalation of lithium ions in the secondary particles and improve the kinetic performance of the electrochemical device.

[0038] In some embodiments, the lithium transition metal composite oxide has a layered crystal structure belonging to the R-3m space group. In some embodiments, the lithium transition metal composite oxide includes Li x1 M x2 Ni y1 Co y2 Mn y3 R y4 B y5 O z1 T z2, 0.6 ≤ x1 ≤ 1.2, 0.01 ≤ x2 ≤ 0.15, 0.3 ≤ y1 ≤ 0.7, 0 ≤ y2 ≤ 0.3, 0.3 ≤ y3 ≤ 0.7, 0 ≤ y4 ≤ 0.2, 0 < y5 ≤ 0.1, 1.8 ≤ z1 ≤ 2.2, 0 ≤ z2 ≤ 0.2, wherein the element M includes at least one of Na or K, the element R includes at least one of Ca, Sr, Ba, Al, Fe, Mg, Si, P, S, Ti, V, Cr, Cu, Zn, Ga, Ge, Zr, Mo, W, Y, Nb, In, Sn, Pb, Sb, Ce, La, Ta or Hf, and the element T includes at least one of F, Cl, Br, I or N.

[0039] In some embodiments, the positive electrode sheet may further include a positive current collector, and in this case, the positive active material layer may be located on one or both sides of the positive current collector. In some embodiments, the positive current collector may include aluminum foil. Of course, other common positive current collectors in the art may also be used. In some embodiments, the thickness of the positive current collector is 7 μm to 20 μm.

[0040] In some embodiments, the positive active material layer may further include a conductive agent and a binder. In some embodiments, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene or carbon nanofibers. In some embodiments, the binder may include at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride - hexafluoropropylene, styrene - acrylate copolymer, styrene - butadiene copolymer, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyethylene ether, polytetrafluoroethylene or polyhexafluoropropylene. In some embodiments, the mass ratio of the positive active material, the conductive agent and the binder in the positive active material layer is (90 - 99):(0.1 - 10):(0.1 - 10), but this is only an example, and any other suitable mass ratio may be used.

[0041] In some embodiments, the negative electrode sheet includes a negative current collector and a negative active material layer. In some embodiments, the negative active material layer may be disposed on one or both sides of the negative current collector.

[0042] In some embodiments, the negative active material layer may include a negative active material, a binder and an optional conductive agent. In some embodiments, the negative active material may include at least one of a carbon material or a silicon - based material. In some embodiments, the carbon material includes at least one of graphite, hard carbon, soft carbon or mesophase carbon microspheres. In some embodiments, the silicon - based material includes at least one of silicon, silicon - oxygen material, silicon - carbon material or silicon - oxygen - carbon material.

[0043] In some embodiments, the binder in the negative electrode active material layer may include at least one of sodium carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, styrene-butadiene rubber, polyurethane resin or acrylate polymer. In some embodiments, the conductive agent in the negative electrode active material layer may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene or carbon nanofibers. In some embodiments, the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode active material layer may be (78 to 98.5): (0.1 to 10): (0.1 to 10). It should be understood that the above is only an example, and any other suitable material and mass ratio may be used. In some embodiments, the negative electrode current collector may be at least one of copper foil, nickel foil or carbon-based current collector.

[0044] In some embodiments, the electrochemical device further comprises a separator disposed between the positive electrode sheet and the negative electrode sheet. In some embodiments, the thickness of the separator is in the range of 3 μm to 20 μm. In some embodiments, the separator comprises a substrate layer and a heat-resistant layer. In some embodiments, the substrate layer comprises at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide or aramid. In some embodiments, the pores of the substrate layer have a diameter in the range of 0.01 μm to 1 μm.

[0045] In some embodiments, the heat-resistant layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. The binder of the heat-resistant layer is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene.

[0046] In some embodiments, the electrochemical device includes a lithium-ion battery, but the application is not limited thereto.

[0047] In some embodiments, the electrochemical device further comprises an electrolyte, the electrolyte comprising a lithium salt and a non-aqueous solvent. In some embodiments, the lithium salt comprises lithium hexafluorophosphate. In some embodiments, the concentration of the lithium salt is 1 mol / L to 2 mol / L. In some embodiments, the non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, or a combination thereof.

[0048] In certain embodiments, carbonate compounds can be linear carbonate compounds, cyclic carbonate compounds or combinations thereof. Examples of linear carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or combinations thereof. Examples of carboxylic acid ester compounds are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, caprolactone, methyl formate or combinations thereof. Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0049] In the second aspect of the present application, an electronic device including the above-mentioned electrochemical device is also provided. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0050] Taking lithium-ion batteries as an example, some specific embodiments and comparative examples are listed below to better illustrate the present application.

[0051] Example 1

[0052] Preparation of negative electrode sheet: artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 96:2:2 and dispersed in deionized water to prepare a negative electrode slurry with a solid content of 0.8. After stirring evenly, the negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil, and dried at 80°C to obtain a negative electrode sheet coated with a negative electrode active material layer on one side. Repeat the above steps on the other side of the copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides. After cold pressing, striping and welding of the pole ears, the negative electrode sheet is obtained.

[0053] Preparation of positive electrode sheet: positive electrode active material, conductive carbon black, carbon nanotubes and polyvinylidene fluoride are mixed in a mass ratio of 93.7:2.8:1.2:2.3 and dispersed in N-methylpyrrolidone to prepare a positive electrode slurry with a solid content of 0.7. After fully stirring and mixing, the positive electrode slurry is evenly coated on one side of the positive electrode current collector aluminum foil, and dried at 85°C to obtain a positive electrode sheet coated with a positive electrode active material layer on one side. Repeat the above steps on the other side of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. After cold pressing, striping, and welding of the pole ears, the positive electrode sheet is obtained.

[0054] The steps for preparing the positive electrode active material are as follows:

[0055] 1) A mixed solution containing NiSO4 and MnSO4 is prepared according to the element molar ratio Ni:Mn=50:50, and the mixed solution is mixed with a precipitant (NaOH solution) and a complexing agent (ammonia water) for reaction, and the reaction time is controlled to be 60 hours, the ammonia concentration is 1 mol / L, and the pH value is 12.2 to obtain a nickel-manganese precursor TM(OH)2 (TM=Ni / Mn) with an average particle size Dv50 of 11 μm;

[0056] 2) Grind and mix the nickel-manganese precursor and sodium carbonate in a molar ratio of Na:(Ni+Mn) of 1.05:1. Calcine at 800°C in air for 20 hours, and then crush, screen and demagnetize to obtain product 1;

[0057] 3) mixing the product 1 with a mixture of lithium hydroxide and lithium nitrate (molar ratio of 1:1), wherein the mass ratio of the mixture of lithium hydroxide and lithium nitrate to the product 1 is 10:1, heating to 400°C at a rate of 10°C / min, maintaining for 6 hours, and quenching to room temperature in a mixture of Ar and air (the volume ratio of Ar to air is 1:2) at a cooling rate of 50°C / min to obtain the product 2;

[0058] 4) washing and soaking the product 2 in deionized water, and drying; crushing and sieving to obtain the product 3;

[0059] 5) Grind and mix the product three with boric acid in a molar ratio of B:(Ni+Mn) a / (b+c) of 0.034:1, and calcine at 200° C. in an air atmosphere for 12 h to obtain a positive electrode active material.

[0060] Preparation of isolation membrane: Porous polyethylene (PE) film is selected as the isolation membrane.

[0061] Preparation of electrolyte: In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC): propyl propionate (PP): ethyl propionate (EP) are uniformly mixed in a mass ratio of 1:1:1:1:1, lithium hexafluorophosphate is added, and the mixture is uniformly mixed to prepare an electrolyte, wherein the mass percentage of lithium hexafluorophosphate in the electrolyte is 12.5%.

[0062] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, shaping, etc.

[0063] Examples 2 to 5

[0064] The difference from Example 1 is that the amount of source B added in step 5) is adjusted according to a / (b+c) shown in Table 1, and the rest is the same as Example 1.

[0065] Examples 6 to 9

[0066] The difference from Example 1 is that the holding time in step 3) is adjusted to 10 hours, 8 hours, 5 hours and 4 hours respectively, so as to adjust d / (b+c) in the positive electrode active material. The rest is the same as Example 1.

[0067] The difference between Comparative Example 1 and Example 1 is that the B coating treatment in step 5) is not performed.

[0068] The difference between Comparative Example 2 and Example 1 is that the nickel manganese precursor and lithium carbonate in step 1) are ground and mixed evenly according to a molar ratio of Li: (Ni + Mn) of 1.02, calcined at 800°C in an air atmosphere for 20 hours, cooled to room temperature at a rate of 10°C / min, and crushed and sieved to obtain product 1; product 1 and boric acid are ground and mixed evenly according to a molar ratio of B: (Ni + Mn) a / (b+c) of 0.034:1, and calcined at 200°C in an air atmosphere for 12 hours to obtain a positive electrode active material.

[0069] In addition, in this application, the following method is used to measure the corresponding parameters.

[0070] 1) Particle morphology and average diameter:

[0071] The positive electrode sheet was cut longitudinally using ion polishing, and then the morphology of the positive electrode active material particles in the cross section of the positive electrode sheet was observed using a scanning electron microscope (instrument model: ZEISS SEM, acceleration voltage: 0.1KV to 30KV). In the cross section, 50 positive electrode active material particles were randomly selected, and the average value of their longest diameters was taken as the average diameter of the positive electrode active material.

[0072] 2) Element content:

[0073] Use a mixed solvent to dissolve the positive electrode active material or negative electrode sample (for example, 0.4g sample uses 10ml of aqua regia (nitric acid and hydrochloric acid mixed in a ratio of 1:1) and 2ml of HF mixed solvent), dilute to 100mL, and then use an ICP analyzer to test the content of elements such as Li, Ni, Mn, B, Na and K in the solution. 3) X-ray diffraction:

[0074] The lithium-ion battery was charged to a fully charged state, disassembled to obtain the positive electrode sheet, and the positive electrode sheet was subjected to X-ray diffraction analysis using an X-ray diffractometer (instrument model: Bruker D8 ADVANCE, target material: Cu Kα, scanning angle: 15-70°).

[0075] 4) Discharge capacity test:

[0076] The lithium-ion battery is first charged at a constant current of 0.5C at a constant temperature of 25°C. After charging to 4.35V, it is charged at a constant voltage to a current of 0.05C. Then, it is discharged at a constant current of 0.2C to 2.8V. The discharge gram capacity = the discharge capacity at 0.2C / the mass of the positive electrode active material.

[0077] 5) Cycle performance test:

[0078] First, in an environment of 45°C, the first charge and discharge were performed, first using a constant current charge of 0.5C to charge to 4.35V, then constant voltage charge to a current of 0.05C, and then constant current discharge at a current of 0.5C to discharge to 2.8V. Repeat the above charge and discharge cycles, and record the discharge capacity of the third cycle and the discharge capacity of the 500th cycle.

[0079] 45° C. cycle capacity retention rate=(discharge capacity at the 500th cycle / discharge capacity at the 3rd cycle)×100%.

[0080] 6) High temperature storage performance test:

[0081] First, the lithium-ion battery is charged with a constant current of 0.5C at 25°C. After charging to 4.35V, it is charged with a constant voltage to a current of 0.05C. The thickness of the lithium-ion battery is measured with a micrometer, and the thickness of the lithium-ion battery at this time is defined as the initial thickness H0 of the lithium-ion battery. The lithium-ion battery is then stored in a constant temperature box at 85°C for 24 hours, and the thickness of the lithium-ion battery is measured using the same method. The thickness of the lithium-ion battery after storage is defined as H1.

[0082] 85℃ thickness expansion ratio = (H1-H0) / H0×100%.

[0083] Table 1 shows various parameters and evaluation results of Examples 1 to 9 and Comparative Examples 1 to 2.

[0084] Table 1

[0085]

[0086]

[0087] By comparing Examples 1 to 5 and Comparative Example 1, it can be seen that the high temperature cycle capacity retention rate and high temperature storage thickness expansion rate of the lithium ion batteries of Examples 1 to 5 are significantly improved compared with the positive electrode active material without B.

[0088] By comparing Examples 1 to 9 and Comparative Example 2, it can be seen that, relative to the positive electrode active material not containing M, the lithium ion batteries of Examples 1 to 9 can have both a higher discharge gram capacity and a higher cycle capacity retention rate and a lower high-temperature storage thickness expansion rate. The possible reason is that, on the one hand, the lithium layer doped with the M element in the positive electrode active material can greatly improve the structural stability of the positive electrode active material under a high delithiation state; on the other hand, the M element introduced into the positive electrode active material will dissolve from the positive electrode during the formation and subsequent charge and discharge processes, and will be deposited on the negative electrode through the electrolyte, so that the solid electrolyte interface (SEI) film component on the negative electrode surface contains carbonates of the M element. The carbonates of the M element have a high electron affinity, which promotes the continuous growth of the SEI film, optimizes the film formation process of the SEI film on the negative electrode surface, and makes the formed SEI film more dense and stable, while improving the viscoelasticity and flexibility of the SEI film and reducing surface cracks. In addition, the carbonate of the M element can enhance the Li + It can also reduce the decomposition and gas production of the electrolyte on the negative electrode side during cycling and high-temperature storage, thereby improving the cycling performance and high-temperature storage performance of lithium-ion batteries.

[0089] In addition, by comparing Examples 1 to 5, it can be seen that the content of B element in the positive electrode active material satisfies 0.01≤a / (b+c)≤0.1, and the lithium ion battery can have both high discharge capacity and excellent high temperature cycle performance and high temperature storage performance. By comparing Example 1 with Examples 6 to 9, it can be seen that the positive electrode active material satisfies 1.7≤I A / I B ≤2, lithium-ion batteries have a high discharge capacity per gram, and their high-temperature cycle performance and high-temperature storage performance are even better.

[0090] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.

Claims

1. An electrochemical device, characterized in that A positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material layer, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises a lithium transition metal composite oxide, the lithium transition metal composite oxide contains Ni element, Mn element, B element and M element, wherein the M element comprises at least one of Na element and K element; The electrochemical device is charged and discharged with a current of 0.2C, and a curve of a relationship between a capacity-voltage differential dQ / dV and a voltage V during discharge of the electrochemical device has a characteristic peak above 4.1V.

2. The electrochemical device according to claim 1, characterized in that In the lithium transition metal composite oxide, the molar content of the B element is a, the molar content of the Ni element is b, the molar content of the Mn element is c, and the molar content of the M element is d, and at least one of the following conditions is satisfied: (1) 0.01≤a / (b+c)≤0.1; (2) 0.01≤d / (b+c)≤0.15; (3)0.3≤b / (b+c)≤0.

7.

3. The electrochemical device according to claim 2, characterized in that At least one of the following conditions is met: (1) 0.02≤a / (b+c)≤0.07; (2)0.03≤d / (b+c)≤0.

08.

4. The electrochemical device according to claim 1, characterized in that The electrochemical device satisfies at least one of the following conditions: (1) The electrochemical device further comprises a negative electrode plate. When the electrochemical device is in a fully charged state, the molar content of the M element in the negative electrode plate is e, and the molar content of the Li element is f, satisfying: 0.03≤e / f≤0.09; (2) When the electrochemical device is in a fully charged state, the molar content of the M element in the lithium transition metal composite oxide is g, and the molar content of the Li element is h, satisfying: 0.02≤g / h≤0.

1.

5. The electrochemical device according to claim 1, characterized in that When the electrochemical device is in a fully charged state, the positive electrode plate is characterized by X-ray diffraction, and has a diffraction peak A in the range of 36° to 37.5°, and the peak intensity of the diffraction peak A is I A , having a diffraction peak B in the range of 43.5° to 45°, and the peak intensity of the diffraction peak B is I B , satisfying: 1.7≤I A / I B ≤2.

6. The electrochemical device according to claim 1, characterized in that The lithium transition metal composite oxide includes a matrix and a coating layer, wherein the matrix contains Ni element, Mn element and M element, and the coating layer contains B element.

7. The electrochemical device according to claim 6, characterized in that The coating layer includes a B-containing oxide.

8. The electrochemical device according to claim 1, characterized in that The lithium transition metal composite oxide includes secondary particles composed of primary particles, and satisfies at least one of the following conditions: (1) The average diameter of the secondary particles is 6 μm to 14 μm; (2) The interior of the secondary particles includes pores; (3) The secondary particles have gaps extending from the inside to the surface.

9. The electrochemical device according to claim 1, characterized in that At least one of the following conditions is met: (1) The lithium transition metal composite oxide has a layered crystal structure belonging to the R-3m space group; (2) The lithium transition metal composite oxide includes Li x1 M x2 Ni y1 Co y2 Mn y3 R y4 B y5 O z1 T z2 , 0.6 ≤ x1 ≤ 1.2, 0.01 ≤ x2 ≤ 0.15, 0.3 ≤ y1 ≤ 0.7, 0 ≤ y2 ≤ 0.3, 0.3 ≤ y3 ≤ 0.7, 0 ≤ y4 ≤ 0.2, 0 < y5 ≤ 0.1, 1.8 ≤ z1 ≤ 2.2, 0 ≤ z2 ≤ 0.2, wherein the element M includes at least one of Na or K, the element R includes at least one of Ca, Sr, Ba, Al, Fe, Mg, Si, P, S, Ti, V, Cr, Cu, Zn, Ga, Ge, Zr, Mo, W, Y, Nb, In, Sn, Pb, Sb, Ce, La, Ta or Hf, and the element T includes at least one of F, Cl, Br, I or N.

10. An electronic device comprising the electrochemical device according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrochemical device and electronic device

    CN113299903A

  • Secondary battery and electric equipment

    CN116525983A

  • Positive electrode material, electrochemical device, and electronic device

    CN116802841A

  • Positive electrode active material and method of producing the same

    JP2021015790A

  • Layered-oxide positive electrode active material and positive electrode plate, sodium-ion battery, and electric apparatus containing same

    US20230238518A1